Analisis Keterlambatan Pembayaran Kepada Vendor PT. X di Surabaya (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the causes of late payments to vendors and evaluate their impact on the operational efficiency of PT. X in Surabaya. Delays in vendor payments can disrupt cash flow and hinder business processes, making it essential to understand the root causes in order to develop appropriate solutions. The research employs a descriptive qualitative approach, with data collected through direct interviews with the finance team, particularly the Account Payable division, and the warehouse department. The findings reveal that payment delays are caused by several factors, including differences in vendor payment terms, the absence of a company reminder system, the lack of written standard operating procedures (SOP), and issues in the document verification process. These delays significantly affect the company's operational efficiency, such as disruptions in monthly financial closing and increased administrative workload. The study recommends the establishment of formal SOPs, the implementation of automated reminder systems, and the standardization of vendor payment terms to improve the efficiency of vendor payment management.